Identifying sustainable lifestyle strategies for maintaining good glycemic control: a validation of qualitative findings - Susan C Weller; Benjamin N Vickers (BMJ Open Diabetes Research & Care)
Introduction Diabetes self-care practices are less effective outside of controlled research settings, and almost half of patients do not achieve good glycemic control. Qualitative studies suggest some lifestyle strategies may be linked to good control, but those strategies have not been validated. This study provides population-based evidence that dietary strategies identified in qualitative studies are associated with glycemic control in US patients with diabetes.Research design and methods In a cross-sectional sample of the National Health and Nutrition Examination Survey (NHANES), qualitative self-management themes were matched to survey questions and used to predict good glycemic control (hemoglobin A1c <7.0% (53 mmol/mol)). Patients were limited to those 50 years of age and older with a diagnosis of diabetes for at least 1 year (N=465).Results Patients averaged 65 years of age with a body mass index of 32.56 kg/m2 and 42% reported no physical activity. In logistic regression models controlling for sociodemographic and medical history variables, self-monitoring of blood glucose, weight loss, and physical activity were not significantly associated with glycemic control. Instead, dietary practices such as consuming low-calorie foods (OR=4.05, 95% CI 1.64 to 10.01), eating less fat (OR=2.15, 95% CI 1.03 to 4.47), and reducing sodium (OR=1.94, 95% CI 1.18 to 3.17) were significantly associated with good glycemic control, as was diabetes education or consultation with a dietitian (OR=3.48, 95% CI 1.28 to 9.45). Non-adherence to medications (OR=0.27, 95% CI 0.11 to 0.68) and general dietary descriptions, such as following a ‘diabetic diet’ (OR=0.32, 95% CI 0.17 to 0.57) and ‘changing eating habits for weight loss’ (OR=0.34, 95% CI 0.15 to 0.77), were associated with poorer glycemic control.Conclusions The NHANES validation of lifestyle management strategies suggests practices that may be sustainable. In a population that tends to be obese with low physical activity, successful self-care might emphasize specific dietary practices offering concrete touchpoints for patient communication and guidance. These strategies might help maintain glycemic control.